Preparation and preclinical evaluation of 18F-labeled folate-RGD peptide conjugate for PET imaging of triple-negative breast carcinoma - Subhani M. Okarvi; Yousef Maliki (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Simultaneous targeting of RGD and FA receptors on breast carcinoma could improve the diagnostic outcome of breast cancer patients. In this study, we have designed and synthesized an FA-RGD heteromeric targeting vector, with both RGD and FA motifs, in one single molecule for positron emission tomography (PET) diagnostic imaging of breast carcinoma. Results Aoa-FA-RGD peptide conjugate was radiolabeled efficiently with [18F]FDG, resulting in high labeling efficiency (≥ 85%). The in vitro stability of the radiotracer in human plasma was found to be high. The Aoa-FA-RGD peptide conjugate showed the nanomolar affinity (≤ 51 nM) to the TNBC MDA-MB-231 cell line. In the MDA-MB-231 xenografts model, [18F]FDG-Aoa-FA-RGD peptide conjugate exhibited efficient clearance from the blood and excretion predominantly by the renal pathway (~ 56% ID), possibly due to its hydrophilic nature. A rapid accumulation of 3.30% ID/g in the TNBC MDA-MB-231 tumors was observed at 45 min p.i. Whereas a low accumulation of radioactivity was seen in the normal organs, including the heart, lungs, liver, stomach, spleen, intestines, and kidneys (< 4% ID/g). The receptor specificity of the radiotracer was confirmed by the receptor-blocking assay. A rapid and efficient tumor targeting, together with the favorable pharmacokinetics, highlights the tumor-targeting potential of the radiofluroconjugate. Furthermore, PET imaging provided sufficient visualization of MDA-MB-231 tumors in mice. Conclusions Our findings suggest that the [18F]FDG-labeled FA-RGD peptide conjugate can be a useful agent for the efficient targeting of TNBC cells. This study suggests the potential of this innovative heteromeric targeting agent for rapid and efficient targeting of tumors and merits further advancement.